Zinc and copper levels are not correlated with angiographically-defined coronary artery disease in sudanese patients - Lutfi, Mohamed F.; Elhakeem, Ramaze F.; Khogaly, Raga S Khogaly S.; Abdrabo, AbdElkarim A.; Ali, Ahmed B.; Gasim, Gasim I.; Adam, Ishag (Frontiers in Physiology, 2015)
A cross sectional study was conducted in El-Shaab Hospital, Sudan to investigate zinc and copper in angiographicaly-defined obstructive (CAD) in patients undergoing elective coronary angiography. One hundred and forty two patients were enrolled. Socio-demographic, medical characteristics were gathered using a questionnaire. Glucose, lipid, zinc, copper levels were investigated using the suitable lab methods. Out of 142, 102 (71.8%) and 40 (28.2%) patients had CAD and patent coronary arteries, respectively. There was no significant difference in the median ( inter-quartiles) zinc [118.5 (97.2 - 151.0) vs. 130.0 (106.0 - 174.0) µg/ml, P = 0.120], copper [150.6 (125.0 - 183.0) vs 158(132.0- 180.0) µg/mL, P = 0.478] levels between the patients with CAD and patent coronary arteries. Likewise, in linear regression analysis there was no associations between zinc, copper levels and CAD. Thus the current study failed to show a significant association between zinc, copper levels and CAD .